Implications of COVID-19 Vaccine Hesitancy: Results of Online Bulletin Board Interviews - Jack M. Gorman; Sara E. Gorman; William Sandy; Nellie Gregorian; David A. Scales; David A. Scales (Frontiers Media S.A., 2022)
Reluctance to accept vaccination against COVID-19 poses a significant public health risk and is known to be a multi-determined phenomenon. We conducted online focus groups, or "bulletin boards," in order to probe the nature of COVID-19 vaccine hesitancy and its implications. Participants were 94 individuals from three distinct U.S. geographical areas and represented a range of demographic and socioeconomic characteristics. Six themes emerged from the 3 day-long bulletin boards: the most trusted source of health information sought is the personal physician; information about health is nevertheless obtained from a wide variety of sources; stories about adverse side effects are especially "sticky"; government health institutions like CDC and FDA are not trusted; most respondents engaged in individualistic reasoning; and there is a wide spectrum of attitudes toward vaccination.